1996
DOI: 10.1111/j.1440-1746.1996.tb00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine ‘Sho‐saiko‐to’ induces tumour necrosis factor‐α and granulocyte colony‐stimulating factor in vitro in peripheral blood mononuclear cells of patients with hepatocellular carcinoma

Abstract: 'Sho-saiko-to' (TJ-9) is a Japanese herbal medicine that is commonly administered to patients with chronic viral liver disease in order to improve their overall physical condition and to prevent the development of liver cancer, The present in vitro study demonstrated that, by adding TJ-9 to cell cultures, there were dose-dependent increases in production levels of tumour necrosis factor-alpha (TNF-alpha) and granulocyte colony-stimulating factor (G-CSF) in peripheral mononuclear cells of patients with hepatoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
0
20
1
1
Order By: Relevance
“…In liver disease patients, cytokine levels in the serum (1-3), cytokine production levels in peripheral blood mononuclear cells (4)(5)(6)(7)(8), and localization of cytokines in a lesion (9,10) are quite important not only for elucidating the pathogenesis and for understanding the pathophysiology, but also for developing new therapies. Even though measurement methods are not complicated, serum cytokines have not been regarded as immunological markers for use in general laboratory tests (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In liver disease patients, cytokine levels in the serum (1-3), cytokine production levels in peripheral blood mononuclear cells (4)(5)(6)(7)(8), and localization of cytokines in a lesion (9,10) are quite important not only for elucidating the pathogenesis and for understanding the pathophysiology, but also for developing new therapies. Even though measurement methods are not complicated, serum cytokines have not been regarded as immunological markers for use in general laboratory tests (11).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, new cytokines have been identified one after another, and more than 30 cytokines have been reported. Cytokines (1) are glycoproteins; (2) act at a quite low level (pg~ng/ml); (3) mainly act in situ on the produced area; (4) individually express several physiological activities; (5) are produced by various cells; (6) express common activities; (7) sometimes act on each other synergistically or antagonistically; (8) are part of a cytokine network; (9) have inhibitors; and (10) are essential for maintaining the homeostasis of the body, but are also overexpressed under specific conditions such as inflammation, and are related to the development and progression of a disease.…”
Section: Introductionmentioning
confidence: 99%
“…48 Studies of TJ-9 in patients with liver cancer have shown a dose-dependent increase in tumor necrosis factor ␣ (TNF-␣) and granulocyte colony-stimulating factor. 49 Another class of herbal medicines, termed "supplemental medicines" or Hozai, are thought to have immunologic activities, such as activating macrophages or stimulating cytokines. TJ-108 (Ninjin-yomei-to), TJ-41 (Hochu-ekki-to), and TJ-48 (Juzen-daiho-to) have been used extensively in Japan, having been tested in vitro for cytostatic properties.…”
Section: Blended Herbal Formulations and Extractsmentioning
confidence: 99%
“…(Kaneko et al, 1994). Another proposed mechanism is a dose-dependent increase in the production of granulocyte colony-stimulating factor (G-CSF) on peripheral blood mononuclear cells (Yamashiki et al, 1992). The study demonstrated that the classic Chinese medicine formula--XCHT showed promise in relieving liver injury and merits further study.…”
Section: Resultsmentioning
confidence: 99%